Tranexamic acid is associated with improved hemostasis in elderly patients undergoing coronary-artery surgeries in a retrospective cohort study - Wang, Enshi; Wang, Yang; Li, Yuan; Hu, Shengshou; Yuan, Su (Frontiers in Surgery, 2023)
Background: More elderly patients undergo coronary artery bypass surgery (CABG) than younger patients. Whether tranexamic acid (TA) is still effective and safe in elderly patients undergoing CABG surgeries is still unclear. Methods: In this study, a cohort of 7224 patients ≥70 years undergoing CABG surgery were included. Patients were categorized into the no TA group, TA group, high-dose group, and low-dose group according whether TA was administered and the dose administered. The primary endpoint was blood loss and blood transfusion after CABG. The secondary endpoints were thromboembolic events and in-hospital death. Results: The blood loss at 24 hours and 48 hours and the total blood loss after surgery in patients in the TA group were 90 ml, 90 ml, and 190 ml less than those in the no-TA group, respectively (p<0.0001). The total blood transfusion was reduced 0.38-fold with TA administration compared to that without TA (OR=0.62, 95% CI 0.56-0.68, p<0.0001). Blood component transfusion was also reduced. High-dose TA administration reduced the blood loss by 20 ml 24 hours after surgery (p=0.032) but had no relationship with the blood transfusion. TA increased the risk of perioperative myocardial infarction (PMI) by 1.62-fold [p=0.003, OR=1.62, 95% CI (1.18-2.22)] but reduced the hospital stay time in patients who were administered TA compared to that of patients who did not receive TA (p=0.026). Conclusion: We revealed that elderly patients undergoing CABG surgeries had better hemostasis after TA administration but increased the risk of PMI. High-dose TA was effective and safe compared with low-dose TA administration in elderly patients undergoing CABG surgery.